MANAJEMEN EKSTRAKURIKULER KARAWITAN DAN KAITANNYA DENGAN PENANAMAN NILAI-NILAI LUHUR BUDAYA BANGSA - Dwi Wahyu Widayati (LP2M Universitas Sarjanawiyata Tamansiswa, 2018)
Abstract The purpose of this research are to describe about management karawitan extracurricular, to know the factor that supports and influence karawitan extracurricular, to know the result that reached in management karawitan and relation with value of nation culture in SDN Gendengan. The type of research used by researches is qualitative research. This research was conducted at SDN Gendengan, Margodadi, Seyegan, Sleman. Data collection techniques in this study are observation, interview and documentation. Data analysis technique in this research is triangulation data. The result of research abaout management karawitan extracuricular at SDN Gendengan consist of : planning held every new academic that planed such as schedule, material, karawitan extracurricular teacher, student and budget. Organizing in form of structures in which there are personnel according to their duties. Implementation of karawitan extracurrucular is used the teah student in art. The purpose of karawitan extracurricular is to make student to better person in the educational goals. The material given is gending dolanan. The metod is lecture and demonstration. The activity held one a week for every class after intracurricular. Evaluation held every six month consist of the participant and the result of learning. The influence of karawitan extracurricuar is school doens’t have gamelan tools, the distance to the practice place is so far and lack of teachers. The value nation culture through karawitan extracurricular is togetherness, politeness, smoothness, consentration, and tolerance Keywords : management extracurricular, the value is sublime